PERAN KEPALA SEKOLAH DAN IKLIM ORGANISASI DALAM MENINGKATKAN PRODUKTIVITAS KERJA GURU DI SD SE-KECAMATAN CAKRANEGARA - Hapipi, Hapipi; Alimudin, Lalu; Ihtiar Akbar, Hasan (CV. Lafadz Jaya, 2024)
This research aims to find out the role of school principals and organizational climate on teacher work productivity in elementary schools in Cakranegara District. This research is ex-post facto research, in this research there is no treatment of any variables studied by the researcher. The method used in the research is a quantitative approach with an influence test to explain the correlation between the independent variable and the dependent variable. To determine the influence of the role of the school principal and organizational climate in this research, several factors are considered, including: leadership, atmosphere, incentives, work schedule, organizational structure, technology and materials on the organizational climate in the form of openness of behavior, health, interpersonal influence and humanism.